Investigating the performance requirements for proprietary concrete repair materials with respect to durability and cracking resistance - Vukindu, Brian (Department of Civil Engineering, 2021)
The premature deterioration of recently constructed concrete structures leads to the need for remedial measures to reinstate their safety and/or serviceability. Bonded concrete overlays (BCOs) are the most widely used concrete repair technique. The premature failure of these overlays, often manifested by cracking and/or debonding, is common despite their widespread use. There are many repair standards, codes and technical guidelines for BCOs. The performance requirements for BCOs stated in these standards vary. This makes the specification of repair materials difficult. This problem is further compounded by the existence of many proprietary concrete repair materials. The objective of this study was to investigate the performance requirements for proprietary repair mortars on cracking resistance and durability with respect to EN 1504-3:2005. This was achieved through an investigation of the mechanical, durability and transport properties of proprietary repair mortars in the hardened state. The mechanical properties that were tested comprised: compressive strength, tensile strength, elastic modulus, tensile relaxation, restrained shrinkage cracking and drying shrinkage. Durability index tests of OPI, CCI WSI were also done. Twelve proprietary repair mortars were tested in the laboratory. Their chemical and physical characteristics based on the aforementioned material properties were determined. The mortars under investigation exhibited significant differences in their physical properties and chemical composition. A review of the existing performance criteria, as stipulated in EN 1504-3:2005, was also conducted to determine if the repair mortars under investigation conform to the requirements of this code. From the test results it has been noted that the tested proprietary repair materials achieved the compressive strengths as stated by the standard EN 1503-4:2005. 11 of the tested repair materials were categorised as “structural” with only mix P2 being a “non-structural” repair mortar. These results also confirmed the specifications/categorisation from the manufacturers. Mixes PS, PFS, SA, S1, S2, G1, PF1, G2, P1, PF2 and A were categorised as high strength mortars to be used for structural repairs. Mix P2, having a low compressive strength is to be used as a cosmetic repair mortar. Furthermore, it was observed that a high compressive and tensile strength of the overlay does not necessarily translate into a high bond strength. The proprietary repair mortars exhibited low permeability. A review of the EN 1504-3:2005 showed that this code does not specify important crack-determining material parameters such as elastic modulus, tensile relaxation and shrinkage despite the critical role they play in the cracking performance of repair mortars. Further research into the microstructural properties of the proprietary repair materials is recommended to give additional insights into the causes of their different physical properties. This should be combined with on-site observation and testing to identify any potentially problematic macro-scale issues associated with repair mortars, particularly in relation to moisture transmission and retention. Understanding these factors amongst others, are essential to prevent damage to repaired structures by the use of incompatible repair materials.